Effect of Different Doses and Sources of Potassium Fertilizer on Growth Rate and Time of Bulb Formation of Garlic (Allium sativum L.) - Octaviany, Devy; Karno; Fuskhah, Eny (Jurnal Online Pertanian Tropik, 2020)
The purpose of this research was to assess the effect of different potassium doses and fertilizer sources on growth rate and time of bulb formation of garlic (Allium sativum L.). The research was conducted in April to Agustus 2019 in Sidomukti Village, Bandungan District, Semarang Regency and at Ecology and Crop Production Laboratory, Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang. The research used a factorial randomized block design with three groups. The first factor was the dose of potassium fertilizer which consisted of a dose of  60 kg K2O/ha, 120 kg K2O/ha, 180 kg K2O/ha, and 240 kg K2O/ha. The second factor was the source of potassium fertilizer which consisted of KCl, ZK, and KNO3. Parameters that collect were time of bulb formation, growth rate, relative growth rate, and potassium absorption of bulb. The data obtained were analyzed by analysis of variance and obtained further by the Duncan test (Duncan's Multiple Range Test) at a significance level of 5%. The results showed that the application of ZK and KNO3 fertilizers at 240 kg K2O/ha had been able to increase the growth rate and the relative growth rate. The higher dose of fertilizer was increasing of potassium absorption of the bulb and made time of bulb formation getting slower.   References Ahmed, M. E., El-Kader, N. I. A. & Derbala, A.A.E.  (2009). Effect of Irrigation Frequency and Potassium Source on the Productivity, Quality, and Storability of Garlic. Australian Journal Of Basic and Applied Sciences, 3(4), 4490–4497. Alfian, D. F., Nelvia & Yetti, H.  (2015). The Effect of Potassium Fertilizer and Compost Mixture of Oil Palm Empty Bunches with Boiler Ash on Growth and Yield of Onion (Allium ascalonicum L.). Jurnal Agroekoteknologi, 5(2), 1-6. Amiroh, A. (2017). Pengaplikasian dosis pupuk bokashi dan KNO3 terhadap pertumbuhan dan hasil tanaman melon (Cucumis melo L.). Jurnal Saintis, 9(1), 25 - 36. Arisha, H. M. E.,. Ibraheim, S. K. A & El-Sarkassy, N. M. (2017). Response of garlic (Allium sativum L.) yield, volatile oil, and nitrate content to foliar and soil application of potassium fertilizer under sandy soil conditions. Middle East Journal of Applied Sciences, 7(1), 44-56. Aslamiah, I. D., dan Sularno. (2017). Response of growth and production of peanut plants of the addition of organic fertilizer concentration and reduction of an organic fertilizer dosage. Prodising Seminas Nasional Fakultas Pertanian UMJ. BPS. (2018). Statistik Indonesia. Badan Pusat Statistik Republik Indonesia, Jakarta. Gunadi, N. (2009). Kalium sulfat dan kalium klorida sebagai sumber pupuk kalium pada tanaman bawang merah. Jurnal Hortikultura, 19(2),174-185. Hickey, M. (2012). Growing Garlic in NSW Second Edition. Primefact 259. Department of Primary Industries. NSW Government. Australia. Hilal, M.H., Selim, A.M. & El-Neklawy, A.S.  (1992). Enhancing and retarding effect of combined sulfur and fertilizer applications on crop production in different soils. In Proceedings Middle East Sulphur Symposium 12-16 February, Cairo, Egypt. Marschner, P.( 2012). Mineral Nutrition of Higher Plants Third Edition. Elsevier Ltd. Oxford. Nainwal, R. C., Sigh, D., Katiyar, R. S., Sharma, I & Tewari, S. K. (2015). The response of garlic to integrated nutrient management practices in a sodic soil of Uttar Pradesh, India. Journal of Spices and Aromatic Crops, 24(1), 33-36. Putra, A. A. G. (2013). Kajian aplikasi dosis pupuk ZA dan kalium  pada tanaman bawang putih (Allium sativum  L.). Jurnal Ganec Swara, 7(2), 10–18. Setiawati, W., Murtiningsih, R., Sopha, G. A & Handayani, T. (2007). Petunjuk Teknis Budidaya Tanaman Sayuran. Balai Penelitian Tanaman Sayuran. Shafeek, M. R., Nagwa, M. H., Singer, S. M., & El-Greadly, N. H. (2013). Effect of potassium fertilizer and foliar spraying with Ethereal on plant development, yield, and bulb quality of onion plants (Allium cepa L). Journal of Applied Sciences Research, 9(2), 1140-1146. Sholihin, Y., Suminar, E., Rizky, W.H. & Pitaloka, G.G. (2016). Meristem explants growth of garlic (Allium sativum L.) Cv. tawangmangu on various compositions of kinetin and ga3 in vitro. Jurnal Kultivasi, 15(3), 172–179. Sulichantini, E. D. (2016). Effect of plant growth regulator Concentration Against Regeneration Garlic (Allium sativum L) In the Tissue Culture. Jurnal Agrifor, 15(1), 29–38. Suminarti, N.E. (2010). The Effects of N and K Fertilization on the Growth and Yield of Taro on Dry Land. Akta Agrosia, 13(1), 1–7. Uke, K. H. Y., Barus, H & Madauna, I. W.  (2015). Effect of Tuber Sizes and Potassium Dosages on Growth and Production of Shallots var. Lembah Palu. Jurnal Agrotekbis, 3(6), 655 - 661. Utomo, P.S & Suprianto, A. (2019). Respon pertumbuhan dan produksi tanaman bawang merah (Allium ascalonicum L.) varietas thailand terhadap perlakuan dosis pupuk kusuma bioplus dan KNO3 putih. Jurnal Ilmiah Hijau Cendekia, 4(1), 28–34. Wu, C., Wang, M., Cheng, Z & Meng, H. (2016). The response of garlic (Allium sativum L.) bolting and bulbing to temperature and photoperiod treatments. Biol Open,  5(4), 507-518.